TEACHING SPEAKING FLUENCY TO JUNIOR HIGH SCHOOL STUDENTS THROUH ANIMATION MOVIE - Rakhmi Amini; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2017)
Speaking is one of the four important elements in English. In order to speak English fluently, speakers need to master sub-skills in speaking English which one of them is fluency. The quality of fluency will be effected to the quality of the conversation. Therefore, fluency is needed to be mastered by the students to avoid mis-understanding in the conversation. Nevertheless, the students in Indonesia tend to have several problems to speak fluently. They are, the students’ anxiety, get influenced by their mother language, word-choosing or lack in vocabulary, and less motivation in learning English. This paper will discuss how to teaching speaking fuency to Junior High School Students through Animation Movie. The content of Animation Movie is pretty easy to be understood by the students in Junior High School and also it will easily interests students and make the students enjoy the learning process so they can overwhelm their problems in order to speak fluently. The use of Animation Movie in teaching speaking fluency to Junior High School students can be implemented by using scientific approach; Observing, Questioning, Associating, Experimenting and Communicating. Key words: Speaking Fluency, Animation Movie